Analisis Dispensasi Nikah Di Kabupaten Sinjai - Awaru, Andi Octamaya Tenri; Kamaruddin, Syamsu A; Najamuddin, Najamuddin (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2025)
Child marriage remains a persistent social phenomenon in Sinjai Regency, despite the minimum legal age for marriage stipulated in Law No. 16 of 2019. This study aims to analyze the current condition of marriage dispensation applications over the past five years and to identify the key factors driving such applications. Using a quantitative approach, data were collected through a survey of 84 respondents, including couples married through dispensation, parents or guardians who submitted requests, and officials from the Religious Court and the Office of Religious Affairs (KUA). The findings show that socially, marriage dispensation is still perceived as frequently occurring; 59.5% of respondents indicated that applications remain common, even though administrative records show a sharp decline from 385 cases in 2021 to only 2 cases in 2025. This discrepancy highlights a gap between formal records and ongoing social practices, particularly in rural areas. The main factors driving dispensation applications include premarital pregnancy (41.7%), economic hardship (28.6%), and sociocultural pressure (25%) related to safeguarding family honor. Overall, the study demonstrates that marriage dispensation serves as a legally sanctioned social mechanism to address moral, economic, and cultural pressures. Therefore, efforts to prevent child marriage must integrate legal enforcement with educational, cultural, and economic empowerment strategies.